Vitamina B12 y ferritina para el diagnóstico de anemia pacientes adultos mayores - Punina Chimborazo, Jhonny Gustavo (2025)
Anemia in older adults is a common and multifactorial health problem, with an estimated 10% to 30% of this group presenting with anemia, and its frequency increases with age and the presence of chronic diseases. The objective of this literature review was to gather information on vitamin B12 and ferritin levels for the diagnosis of anemia in elderly patients, including laboratory methods and clinical manifestations. It is a documentary, non-experimental research of a retrospective and cross-sectional type. 46 scientific articles were reviewed, of which 30 were selected through inclusion and exclusion criteria. The information was obtained from scientific databases, including Google Scholar, Redalyc, PubMed, ScienceDirect, Journal of Cell Biology, Journal of Contemporary Medicine, WHO, Oceanomedicine, Scielo, ASEI, Geosalud, Ocronos, PAHO, and BVS. Through the analysis and discussion of various authors, the proposed objectives were achieved, demonstrating the effectiveness of immunoassays, particularly chemiluminescence and holotranscobalamin, which surpass the utility of serum B12. The most frequently found clinical manifestations were peripheral neuropathy, cognitive impairment, in addition to classic symptoms such as fatigue and pallor. These can be atypical and subtle on many occasions; therefore, the clinical evaluation must be thorough, considering both the symptoms and the patient's comorbidities, and complemented with precise laboratory tests for an adequate diagnosis and management.